ANALISIS RASM DAN QIRĀ‘ĀT MANUSKRIP TAFSĪR JALĀLAYN KARYA KIAI SAHID PATI - Farida, Umma; Nuzulia, Mitatun (IAIN Syekh Nurjati Cirebon, 2024)
This study aims to explore information and identify the manuscript of Tafsīr Jalālayn by Kiai Sahid located in Tayu, Pati, Central Java by emphasizing the study of writing techniques (rasm) and reading (qirā’āt). This study conducted a literature study (library research) using a philological approach and analyzed using content analysis technique in a critical descriptive manner. The study results found that the manuscript copy of Tafsīr Jalālayn was written by Kiai Sahid. The interpretation of verses in the Javanese language by Kiai Sahid to the manuscript of Tafsīr Jalālayn was carried out in 1966 as a learning medium for students at Islamic boarding schools. The writing technique (rasm) used in this manuscript. The rasm used by Kiai Sahid in writing the manuscript of Tafsīr Jalālayn uses a dictation writing technique (rasm imla'i). Meanwhile, the reading technique (qirā’āt) used in this manuscript is the qirā’āt of Imam Ashim narrated by Imam Ḥafs as the qirā’āt that is popular and widely used in Indonesian society. In addition, the manuscript of Tafsīr Jalālayn by Kiai Sahid is different from the book of Tafsīr Jalālayn by Imam Jalāluddīn al-Suyūṭī and Jalāluddīn al-Maḥallī in terms of its physical condition, from the aspects of binding, sheets, and pages of the manuscript, the number of lines per page and page numbering, the size of the manuscript and writing, illumination, language, script, and type of calligraphy, the color of the writing, rasm, qirā’āt, and scholia. Penelitian ini bertujuan untuk menggali informasi dan mengidentifikasi manuskrip Tafsīr Jalālayn karya Kiai Sahid yang berada di Tayu, Pati, Jawa Tengah dengan menekankan pada kajian teknik penulisan (rasm) dan bacaannya (qirā’āt). Penelitian ini menempuh kajian kepustakaan (library research) dengan menggunakan pendekatan filologi, dan dianalisis menggunakan analisis konten (content analysis) secara deskriptif kritis. Hasil penelitian menemukan bahwa manuskrip salinan Tafsīr Jalālayn ini ditulis oleh Kiai Sahid. Pemberian makna dalam bahasa Jawa (makna pegon) oleh Kiai Sahid terhadap manuskrip Tafsīr Jalālayn ini dilakukan pada tahun 1966 yang bertujuan untuk media pembelajaran para santri di pondok pesantren. Teknik penulisan (rasm) yang digunakan dalam manuskrip ini. Adapun rasm yang digunakan Kiai Sahid dalam penulisan manuskrip Tafsīr Jalālayn ini, yakni menggunakan rasm imlā‘ī. Sedangkan qirā’āt yang digunakan dalam manuskrip ini, yakni qirā’āt Imam ‘Āṣim riwayat Imam Ḥafs sebagaimana qirā’āt yang populer dan banyak digunakan dalam kalangan masyarakat Indonesia. Selain itu, manuskrip Tafsīr Jalālayn karya Kiai Sahid berbeda dengan kitab Tafsīr Jalālayn karya Imam Jalāluddīn al-Suyūṭī dan Jalāluddīn al-Maḥallī secara kondisi fisiknya, dari aspek penjilidan, lembar, dan halaman naskah, jumlah baris setiap halaman dan penomoran halaman, ukuran naskah dan tulisan, iluminasi, bahasa, aksara, dan jenis khat, warna tulisan, rasm dan qirā’āt, dan scholia.